The Impact of Covid-19 Pandemic on Effective Electronic Criminal Trials: A Comparative Study - Orin Gusta Andini; Mahendra Putra Kurnia; Nilasari Nilasari; Garin Bintang Andiki (Lembaga Contrarius Indonesia, 2023)
The widespread spread of COVID 19 influenced various aspects of life in all nations across the globe, including the effect on the judicial and penal systems. People were unable to appear in court because lockdowns were implemented; therefore, electronic court is a solution to such a challenge. This article aims to investigate how the widespread COVID-19 epidemic has affected the efficiency of the of electronic criminal justice proceedings. In addition, this article describes the implementation of an electronic criminal justice system in another country due to the Covid 19 pandemic. The research method employed is normative legal research through a statutory approach and a comparative approach between Indonesia and the Netherlands. The study found that the electronic criminal justice system has been implemented quite effectively, despite the fact that it was still encountering obstacles. In both Indonesia and the Netherlands, technological issues have posed obstacles to the implementation of electronic courts for criminal cases. However, the difference lies in the suspect's and attorneys' responses. While Indonesian attorneys viewed electronic court as beneficial, Dutch attorneys argued that it violates the freedoms of the accused.